Clinical outcomes of pipeline embolization devices with shield technology for treating intracranial aneurysms - Luo, Chao; Jin, Lide; Dong, Jigen; Fu, Zaixiang; Liu, Erheng; Yin, Shi; Jian, Lipeng; Luo, Pengren; Liu, Bo; Huang, Wei; Zhou, Shuai (Frontiers in Neurology, 2022)
Introduction: As a common endovascular treatment for intracranial aneurysms, the pipeline embolization device (PED) is considered a standard treatment option, especially for large, giant, wide-necked, or dissecting aneurysms. A layer of phosphorylcholine biocompatible polymer added to the surface of the PED can substantially improve this technology. This PED with shield technology (pipeline shield) is relatively novel; its early technical success and safety have been reported. We conducted a systematic literature review with the aim of evaluating the efficacy and safety of the pipeline shield. Methods: We searched the PubMed, Embase, and Cochrane databases, following the preferred reporting items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Results: We selected five prospective and two retrospective studies for review. A total of 572 aneurysms were included; of these, 506 (88.5%) were unruptured. The antiplatelet regimens were heterogeneous. The rate of perioperative and postoperative complications was 11.1% (95% confidence interval [CI] 6.5% to 18.9%). The adequate occlusion rate at 6 months was 73.9% (95% CI 69.1% to 78.7%). The adequate occlusion rate of more than 12 months was 80.9% (95% CI 75.1% to 86.1%). The mortality rate was 0.7% (95% CI 0.2% to 1.5%). Subgroup analyses showed that aneurysm rupture status had no effect on aneurysm occlusion rate, patient morbidity, or mortality. Conclusion: This review demonstrates the safety and efficacy of the pipeline shield for treating intracranial aneurysms. However, direct comparisons of the pipeline shield with other flow diverters are needed to better understand the relative safety and effectiveness of different devices.